Original paper High-frequency ultrasonography in monitoring the effects of treatment of selected dermatoses - Polańska, Adriana; Dańczak-Pazdrowska, Aleksandra; Silny, Wojciech; Sadowska, Anna; Jenerowicz, Dorota; Osmola-Mańkowska, Agnieszka; Olek-Hrab, Karolina (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Introduction : High-frequency ultrasound provides a modern, non-invasive method of skin visualization used for many years in dermatology. In this paper, we present the use of high-frequency ultrasound in monitoring the effects of treatment of selected dermatoses and a review of the literature on this topic. Material and methods : Ultrasound examination of the skin using a 20 MHz linear probe (Dermascan C, Cortex) was performed twice: before the introduction of a specific treatment and after therapy in patients treated at the Department of Dermatology, Poznan University of Medical Sciences, with a diagnosis of atopic dermatitis, T-cell cutaneous lymphoma, eosinophilic fasciitis, limited cutaneous scleroderma (morphea), plaque psoriasis and chronic cutaneous graft versus host disease. Results : In each of the patients presented in this study ultrasound skin imaging made it possible to visualize the clinical improvement by analyzing the degree of echogenicity, the thickness of the dermis, hypoechoic band and the entrance echo. Conclusions : We demonstrated the usefulness of 20 MHz ultrasound in monitoring the treatment of different dermatoses.